EVs and renewables: Navigating future sustainability with symmetry and asymmetry - Sahoo M.; Kaushik S.; Gupta M.; Khairul Islam M. (Elsevier Ltd, 2025)
Electric vehicles (EVs) play a pivotal role in enhancing environmental sustainability by significantly reducing greenhouse gas emissions, combating air pollution, and diminishing reliance on fossil fuels. This study meticulously investigates the impact of EVs and renewable energy on ecological and carbon footprints in four emerging economies?Brazil, India, China, and South Africa?from 2010 to 2022. Employing both symmetric and asymmetric panel models, the research assesses the effects of EVs and renewable energy sources on environmental sustainability. The findings indicate a modest yet positive reduction in carbon footprints due to EV adoption in these nations. Similarly, renewable energy sources demonstrate a favorable impact on environmental sustainability. Crucially, the synergy between EVs and renewable energy exhibits a more substantial effect in diminishing ecological and carbon footprints. The study underscores the significance of integrating EVs with renewable energy for charging, emphasizing its pivotal role in achieving environmental sustainability. ? 2024 Elsevier Ltd